2015
DOI: 10.1007/s10661-015-4381-1
|View full text |Cite|
|
Sign up to set email alerts
|

A comparison of various artificial intelligence approaches performance for estimating suspended sediment load of river systems: a case study in United States

Abstract: Accurate and reliable suspended sediment load (SSL) prediction models are necessary for planning and management of water resource structures. More recently, soft computing techniques have been used in hydrological and environmental modeling. The present paper compared the accuracy of three different soft computing methods, namely, artificial neural networks (ANNs), adaptive neuro-fuzzy inference system (ANFIS), coupled wavelet and neural network (WANN), and conventional sediment rating curve (SRC) approaches f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(75 citation statements)
references
References 63 publications
1
73
0
1
Order By: Relevance
“…Therefore, further investigation is required to analyze topographic dependence on denitrification and assimilation in urban areas. In addition, the loading and nitrogen reducing process is ambiguous in urban area and therefore modeling evaluation using fuzzy pattern-recognition may be useful [43][44][45][46].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Therefore, further investigation is required to analyze topographic dependence on denitrification and assimilation in urban areas. In addition, the loading and nitrogen reducing process is ambiguous in urban area and therefore modeling evaluation using fuzzy pattern-recognition may be useful [43][44][45][46].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…These interconnections are adjusted using an error convergence technique so that the network's response best matches the desired response. In general, the main advantage of the ANN technique over traditional methods is that it does not require information about the complex nature of the underlying process under consideration to be explicitly described in mathematical form WANG et al [2009], OLYAIE et al [2015. In the present study, the input and output data have been scaled to make them bounded in the intervals 0 and +1 using the standardization equation as follows:…”
Section: Data Normalizationmentioning
confidence: 99%
“…The results showed that the performances of both particular RBF and MLP models were close to each other and capable to capture the exact pattern of the sediment data in the river. OLYAIE et al [2015] compared the accuracy of three different soft computing methods, namely, artificial neural networks (ANNs), adaptive neuro-fuzzy inference system (AN-FIS), coupled wavelet and neural network (WANN), and conventional sediment rating curve (SRC) approaches for estimating the daily SSL in two gauging stations in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…This would require prior work on searching and obtaining multi-year data history for training the neural networks. Another option for dealing with uncertainty due to data scarcity would be the use of fuzzy sets [29][30][31] .…”
Section: A Estimation Of Photovoltaic Productionmentioning
confidence: 99%